Knowledge and practice in respect of medical solid waste management among healthcare workers at Quang Nam Northern Mountainous Region General Hospital - Nguyen, Cong Xinh; Tran, Van Vui; Nguyen, Thi Dang Thu; Dang, Thi Anh Thu (Tạp chí Y Dược Huế, 2023)
Background: Proper management of medical solid waste (MSW) is a complex global challenge that affects healthcare workers (HW), patients, and the environment. This study aims to evaluate the knowledge and practices of HW regarding MSW management and explore the factors associated with their knowledge and practices at the Quang Nam Northern Mountainous Region General Hospital in 2020. Materials and method: A cross-sectional study was conducted on 478 HW from June to December 2020. A self-administered questionnaire was used to collect general and knowledge information, while a checklist was used to assess their practices. Multivariate logistic regressions were conducted to identify the factors associated with knowledge and practices. Results: Out of the 478 respondents, 71.1% had good general knowledge, and 75.9% had good practices regarding MSW management. Multivariate logistic regressions showed that knowledge was significantly associated with age group (OR = 14.69; 95%CI = 5.87 - 36.77 and OR = 44.26; 95%CI = 12.04 - 162.74, p < 0.001), occupation (OR = 22.78; 95%CI = 4.39 - 118.38 and OR = 18.09; 95%CI = 3.81 - 85.90, p < 0.001), training courses (OR = 0.21; 95%CI = 0.09 - 0.45 and OR = 0.24; 95%CI = 0.09 - 0.65, p < 0.05), and frequency of MSW monitoring activity (OR = 5.08; 95%CI = 2.18 - 10.87, p < 0.001). Similarly, practices were significantly associated with age group (OR = 3.36; 95%CI = 1.35 - 8.38, p < 0.05), working experience (OR = 0.49; 95%CI = 0.25 - 0.94, p < 0.05), and frequency of MSW monitoring activity (OR = 2.81; 95%CI = 1.63 - 4.85, p < 0.001). Furthermore, a positive association was observed between knowledge and practices regarding MSW management. Conclusion: Overall, the study found that the respondents had good knowledge and practices regarding MSW management. To maintain and improve this, the hospital should provide further training courses on MSW, ensure proper monitoring and supervision of managers and HW.